PKM Pelatihan Pemanfaatan Buku Cerita Berbasis Augmented Reality Bagi Guru-Guru SD pada Kelompok Kerja Guru Kecamatan Balusu - Syamsuriyawati; Nasrullah, Ince; Basri, Syamsuriana (BALE LITERASI, 2025)
Digital transformation in education requires teachers to be able to integrate technology into the learning process, including Augmented Reality (AR) technology, which can provide visual and interactive learning experiences. This Community Empowerment Programme (PKM) aims to enhance the understanding and skills of primary school teachers in Balusu Sub-district, Barru Regency, in utilising AR-based storybooks as a learning medium. The programme is implemented through three stages: socialisation, training and mentoring, and evaluation. Training methods include face-to-face workshops, practical sessions on creating AR content using Canva, ChatGPT, and Assembler Edu, as well as technical mentoring. Evaluation was conducted through the distribution of questionnaires, in-depth interviews, and classroom implementation observations. Results showed that 87% of participants understood the steps for creating AR storybooks, 82% felt confident using them in the classroom, and 76% had attempted implementation at least once. 91% of participants expressed satisfaction with the training methods, and 68% demonstrated interest in continuing AR media development independently. Interviews supported these findings, with teachers reporting increased student enthusiasm and motivation to continue innovating, despite facing limitations in devices and time. The programme proved effective in equipping teachers with practical and relevant digital skills and encouraging the adoption of AR-based learning technology. In conclusion, this training contributed positively to strengthening teachers' capacity to create creative, interactive, and contextual learning experiences.